Generalized Almost Periodic Solutions and Generalized Asymptotically Almost Periodic Solutions of Inhomogenous Evolution Equations - Kostić, Marko (Sarajevo Journal of Mathematics, 2018)
The main aim of this paper is to enquire into the existence and uniqueness of generalized almost periodic solutions and generalized asymptotically almost periodic solutions of inhomogenous (semilinear) evolution equations in Banach spaces. We seek for the solutions belonging to the classes of (asymptotically) Weyl-almost periodic functions and (asymptotically) Stepanov almost periodic functions.